2020
DOI: 10.1038/s41467-020-17949-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin fluoroprobe reveals multiple sites of cytokinin perception at plasma membrane and endoplasmic reticulum

Abstract: Plant hormone cytokinins are perceived by a subfamily of sensor histidine kinases (HKs), which via a two-component phosphorelay cascade activate transcriptional responses in the nucleus. Subcellular localization of the receptors proposed the endoplasmic reticulum (ER) membrane as a principal cytokinin perception site, while study of cytokinin transport pointed to the plasma membrane (PM)-mediated cytokinin signalling. Here, by detailed monitoring of subcellular localizations of the fluorescently labelled natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 40 publications
6
60
0
Order By: Relevance
“…10). Similar to previous 11,12 and recent 28 reports, some of the non-ER AHK signal was clearly at the cell surface, indicating plasma membrane localisation. Across multiple imaged cells, 25% of AHK3 and 36% of AHK4 signals were localised in non-ER regions (Fig.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…10). Similar to previous 11,12 and recent 28 reports, some of the non-ER AHK signal was clearly at the cell surface, indicating plasma membrane localisation. Across multiple imaged cells, 25% of AHK3 and 36% of AHK4 signals were localised in non-ER regions (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Although we did not attempt to make detailed quantitation of relative proportions of AHKs on plasma membrane vs ER, our image analysis likewise clearly indicates that significant amounts of AHK are found in non-ER regions including the cell surface. Our data are strongly corroborated by independent experiments showing colocalisation of plasma membrane markers both with AHK4-GFP and with a fluorescently tagged iP derivative that preferentially binds AHK4 28 . Moreover, Kubiasová et al 28 show that AHK4 and tagged iP are found in brefeldin A-dependent endocytic vesicles characteristic of trafficking to and from the plasma membrane.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations